Soil Bentonite Liner to Control Migration of Sodium and Potassium Ions - Kulkarni Megha N.; Ramakrishnegowda C.; Nanda H. S.; Sivapullaiah P.V. (International Journal of Research in Chemistry and Environment (IJRCE), 2016)
Soil liners amended with bentonite can be used for the control and containment of pollutant migration from landfills. Clay liners are preferred because of low hydraulic conductivity and high sorptive characteristics. To know the rates of migration under combined influence of advection and diffusion the required diffusion coefficient and retardation factor of ions like sodium and potassium in suggested soil has been assessed through laboratory column experiments.The breakthrough times of ions in a liner of thickness of 1m,2m under different transport phenomena, are compared.The breakthrough times under similar conditions are varied since process is influenced by the dominant transport mechanism.